Suicides of famous chefs of today: stories and reasons - Oksana Nykyha; Olha Romanchuk; Rostyslav Koval; Myroslava Danylevych; Yuliia Kalymon (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Міжнародні відносини, економіка, країнознавство, туризм)
Suicide and suicidal behavior are one of the key issues for public policy and health care. Well-known American psychiatrist Somya Abubucker states that according to the WHO, a death by suicide occurs every 40 seconds in the world and “there are indications that for every adult person who died by suicide, there could be more than twenty others who attempted to commit it”. Restaurants remain a highly stressful environment, with the chef profession ranking among the top 10 most nerve-racking jobs in the world. The aim of the article is to present the life story and professional activity of the world’s most famous chefs and restaurateurs who committed suicide over the past 30 years, as well as the analysis of the probable reasons for their actions. To achieve the declared goal, the following research methods were used: historical, descriptive, comparative, systematization and generalization. The chefs in question used to work in the best restaurants in the United States, Canada, France, Italy, Switzerland, Great Britain and Australia. They made a significant contribution to the development of world gastronomy, their establishments have been transformed into truly cult locations, awarded stars from «Michelin» and evaluations from «Gault & Millau», which have been operating for several decades and offering the most exquisite dishes. It was established that the reasons for their suicides were mostly depression, emotional exhaustion and burnout, economic crisis, a drop in profits and lower ratings, loss of a loved one / close person, influence of reality shows, constant pressure, irregular work schedule, unjustified accusations. It was found that among the methods of suicide, it is, in particular, hanging, use of firearms, drowning and suffocation, medicine and drug overdose. The motives of the actions of some of them remained a mystery, since not even suicide notes were found. Priorities for suicide prevention include increasing specialized mental health programs, restricting access to weapons, and strengthening surveillance to detect signals / reports / information that a person is exhibiting suicidal intent. The obtained results make it possible to supplement and expand specialized training courses in higher education institutions of Ukraine, where personnel are trained for the field of tourism, hotel and restaurant industry, as well as medicine (in particular, psychology, psychiatry, addictionology and rehabilitation).